Analysis of Kembangan Regional Hospital Marketing Strategies - Parulian Thomas; Wahyu Sulistiadi; Puput Oktamianti (International Journal Labs, 2023)
The primary objective of this research is to develop a comprehensive marketing strategy for Kembangan Regional Hospital through a thorough SWOT analysis. The study aims to determine effective segmentation, targeting, and positioning strategies for the hospital, coupled with an examination of the current marketing mix. By employing Operational Research within a qualitative methodological framework, the research seeks to derive valuable insights for optimizing strategic alternatives in the realm of healthcare services. Data collection involved a survey of 40 outpatients at the hospital and utilized Focus Group Discussions (FGD) with various sources and observational methods. The purposive sampling method was employed to select informants for a more targeted and insightful analysis. FGD results revealed a robust internal situation for Kembangan Hospital and identified numerous external opportunities, outweighing potential threats. In terms of service products, the hospital has demonstrated innovation by enhancing existing services, including prompt Medical Check-Up (MCU) services, specialized treatment options for TB-RO and MDR patients, and dedicated services for HIV patients. The shift from conventional to digital promotional media has been recognized, with the utilization of social media and other digital platforms to enhance outreach and engagement. This research sets the stage for formulating optimal marketing strategies that align with the strengths and opportunities identified, fostering the continued growth and success of Kembangan Regional Hospital in the competitive healthcare landscape.